Imaging features of various complications of preterm birth: experience from a tertiary center in north India and review of literature - Poonam Sherwani; Prateek Kumar Panda; Namrata Bagchi (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Preterm birth (PTB) is an essential health-related concern worldwide and is one of the crucial causes of infant mortality and morbidity. Incidence and prevalence in India are relatively high and are on an increasing trend. Various predisposing factors for preterm birth are essentially the same all over the world; however, a few potential factors, like inadequate antenatal care and low socio-economic status, are a few other contributing factors leading to preterm birth in India. To address the health repercussions associated with PTB, it is essential to recognize the detrimental effects of PTB and to provide preconception counseling to mothers who are at high risk of PTB. In this review article, we will address the prevalence and risk factors of preterm neonates in India and their related complications and sequelae, with their salient imaging features.